The Photochemistry of Functionalised Rhenium (I) Tricarbonyl Complexes - Akabar, Nurshadrina (Curtin University, 2017)
This research explores the fundamental photochemistry of neutral and cationic rhenium(I)-NHC complexes with formula [Re(N^C)(CO)3(L)]+/0, where N^C represents a bidentate N-heterocyclic carbene ligand and L resembles various pyridine substituents. In addition, rhenium(I) phen tetrazolato complexes with formula [Re(phen)(CO)3(L)], where phen is 1,10-phenanothroline and L represents a tetrazolato moiety coordinated to various amino acids are studied. The basis of this research is to study the potential effect of electron transfer on the photophysics of rhenium(I) complexes.